My robot ate my homework - Krulik, Nancy E.; Burwasser, Amanda Elizabeth (Krulik, Nancy E. Project droid, 2017)
"Logan has been using his robot cousin, Java, to do his homework, but when their teacher announces a geography bee, Logan realizes he'll have to study or be discovered"--